Preventing chronic diseases : a vital investment (WHO, 2005)
Chronic diseases - the major causes of premature adult deaths in all regions of the world - have been generally neglected on the international health and development agenda. WHO is launching a global report on chronic diseases, which will present the latest scientific information and make the case for increased and urgent action for chronic disease prevention and control. The report will review the burden of chronic diseases, major risk factors and associated trends. It will be an authoritative and state-of-the-art guide to effective and feasible interventions. The primary audience of the report will be health planners and decision-makers as well as stakeholders who can influence multisectoral government action.
Keywords: epidemiologie; Chronic Disease; Investments; Evidence-Based Medicine; investice; veřejné zdravotnictví; lékařství; Public Policy; mezinárodní spolupráce; International Cooperation; chronická nemoc; veřejná politika; medicína založená na důkazech